2011
DOI: 10.1289/ehp.1002238
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Concentrations of Parabens and Serum Hormone Levels, Semen Quality Parameters, and Sperm DNA Damage

Abstract: BackgroundParabens are commonly used as antimicrobial preservatives in cosmetics, pharmaceuticals, and food and beverage processing. Widespread human exposure to parabens has been recently documented, and some parabens have demonstrated adverse effects on male reproduction in animal studies. However, human epidemiologic studies are lacking.ObjectiveWe investigated relationships between urinary concentrations of parabens and markers of male reproductive health in an ongoing reproductive epidemiology study.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
170
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(192 citation statements)
references
References 42 publications
10
170
1
2
Order By: Relevance
“…The epidemiological studies investigating a link between male BPA exposure and inhibin B levels are far from providing a clear picture. Urinary BPA was found to be inversely associated with inhibin B levels measured in the serum of the male partners in subfertile couples (Meeker et al, 2011). Furthermore, male workers in the highest quartile of BPA measurements had lower inhibin B levels (Liu et al, 2015).…”
Section: Inhibin Bmentioning
confidence: 90%
“…The epidemiological studies investigating a link between male BPA exposure and inhibin B levels are far from providing a clear picture. Urinary BPA was found to be inversely associated with inhibin B levels measured in the serum of the male partners in subfertile couples (Meeker et al, 2011). Furthermore, male workers in the highest quartile of BPA measurements had lower inhibin B levels (Liu et al, 2015).…”
Section: Inhibin Bmentioning
confidence: 90%
“…After exposure, environmental phenols, like any other non-persistent compounds, have short halflives (~6-12 hours). Therefore, concentrations of these compounds in spot samples (urine or serum/plasma) primarily reflect exposure(s) which occurred within a relatively short period preceding sample collection (58) and there is considerable temporal variability of concentrations in spot samples (59,60). The variability of serum concentrations from spot sampling plus the higher concentrations of some phenols in non-Hispanic blacks may have contributed to the higher standard errors for this particular ethnic group.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown an association between human exposure to parabens and adverse health outcomes (Meeker et al 2011;Savage et al 2012). In March 2011, Denmark has banned the application of propyl paraben, butyl paraben, and their salts in cosmetic products for children under 3 years old (Asimakopoulos et al 2014).…”
Section: Responsible Editor: Hongwen Sunmentioning
confidence: 99%